Voltammetric Determination of 6-Mercaptopurine in Drugs and Blood Using a Glassy Carbon Electrode Modified with Chromium(III)hexacyanoferrate(II) - Hajian, R.; Azarkish, A.; Shams, N. (Asian Journal of Chemistry, 2011)
A Cr(III) hexacyanoferrate(II) (CrHCF)-modified glassy carbon electrode was used to determine 6-mercaptopurine in some drugs and blood by cyclic voltammetry. The influence of several parameters on the voltammetric electrode response was analyzed. The linear dynamic range was 2.30 × 10-7 mol L-1 to 7.27 × 10-6 mol L-1 of mercaptopurine, with r = 0.9976. The limit of detection was 1.3 × 10-7 mol L-1. The voltammetric proposed method for determination of 6-mercaptopurine presented good accuracy and the experimental results demonstrated that the CrHCF-modified glassy carbon electrode has a large potential for the analysis of 6-mercaptopurine in real samples. Furthermore, it has the advantages of a fast response, a low detection limit, low cost, and simple development and application.